Cordate-shaped UWB-MIMO antenna with notch band characteristic and high isolation. (25th January 2021) - Pannu, Preeti; Sharma, Devendra Kumar
Abstract : Purpose: This paper aims to design a most demanding low profile and compact ultra-wide band (UWB) antenna system for various wireless applications. The performance (in terms of data rate) of UWB system is improved by using multiple-input-multiple-output (MIMO) technology with it. Owing to the overlap of other existing licensed bands with that of UWB, electromagnetic signals can interfere. So, notched band UWB MIMO antenna system reported here which is highly compact, bandwidth efficient, superior data rate and high inter-element isolation comparatively to other reported designs. Design/methodology/approach: A 49 × 49 × 1.6 mm 3 quad-port UWB MIMO antenna with specific bandwidth elimination property is designed. The proposed planar MIMO configuration comprises unique four identical "Cordate-shaped" monopole radiators fed by 2.3-mm thick microstrip-lines. The radiators are located right-angled to each other to enhance inter-element isolation. Further, a different approach of slitted-substrate is applied to minimize the overall size and mutual coupling of the MIMO antenna, as a substitute of decoupling and matching structures. The defected ground structure is used to obtain −10 dB impedance bandwidth in entire UWB band, without compromising with the lower cut-off frequency response. Further, to eliminate the undesired resonant band (WLAN at 5.5 GHz) from UWB, a rounded split ring resonator is introduced in monopole patch. Findings: In the entire operating band of 2.8 to 11 GHz, isolation among elements is more than 24 dB, envelope correlation coefficient less than 0.002, diversity gain greater than 9.99 dB and TARC less than −7 dB are obtained at all 4-ports. Research limitations/implications: The measured parameters of the fabricated prototype antenna on FR4 substrate are found in good agreement with the simulated results. The small variation in software results and hardware results are observed due to hardware design limitations. Practical implications: The proposed design may be used for any wireless application following in the range of UWB. Originality/value: It can be shown from graphs of measured parameters of the fabricated prototype antenna. They found to be in good agreement with the simulated results.